Comparison of the Cytotoxic Activities of Stachys Lavandulifolia and Stachys Cataonica Species - Yuce, Hande; Ozgen, Ridvan; Gurhan, Ismet; Ozek, Dilan Askin; Sahin, Yasemin; Tanbek, Kevser; Sandal, Suleyman (Wiley, 2025)
[Abstract Not Available]
Keywords: Stachys lavandulifolia; Stachys cataonica; Essential oil; Anticancer activity